Analisa Konten Marketing Di Sosial Media Tiktok Terhadap Brand Awareness Bittersweet By Najla - Andry Mochamad Ramdan; Muhammad Fikri Maulana; Muhammad Aqshel Revinzky (Program Studi Ilmu Administrasi Bisnis FISIP UNPAS, 2022)
Digital Marketing is a marketing activity including branding that uses various media. Digital Marketing is also their tool in promoting their business, one of which is by utilizing social media or the term is called Social Media Marketing. Brand awareness or brand awareness is the ability of a prospective customer to be able to recognize a brand that is part of a certain product category. The purpose of this study is to analyze Content Marketing on social media Tiktok on Brand awareness Bittersweet By Najla. The method used in this study is a qualitative method and the data collection technique used in this study is an interview with a phenomenological approach. The data analysis technique used is descriptive data technique and uses triangulation of data sources. So, based on the research conducted, the results obtained are proven that bittersweet by najla increases brand awareness through the content displayed on the bittersweet by najla tiktok platform.